Focal infection theory: past and present - A. V. Patrushev; A. V. Sukharev; A. M. Ivanov; A. V. Samtsov (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
The authors present a historical review of and current data on the role of the focal infection in the human body as well as possible development of systemic diseases against its background.